2022
DOI: 10.16888/interd.2023.40.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Reincidencia delictiva en adolescentes colombianos: factores de riesgo y protectores relacionados

Abstract: The authors are immensely grateful to the Instituto Colombiano de Bienestar Familiar for giving its endorsement and permission for the study (SIM E-2016-660327-0111), the authorities and legal guardians who signed the consent, the institutions that provided their support when applying the instruments, and above all, to the participating adolescents who donated their time and provided the information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…In addition, Borschmann et al, (2020) found that adolescents offenders in custody may face several significant health problems and a higher prevalence rate to conditions and risks such as mental disorders, substance use disorders, neurodevelopmental disabilities, infectious diseases, among others that in addition to impacting their physical and mental health directly impacts their education by placing them at a disadvantage with adolescents who do not have these conditions. In other studies, it has been found that this population has multiple risk factors that may be involved in the recidivism of crimes among those involved are the parents of adolescents by allowing or having a passive or permissive attitude regarding drug use, criminality in family members and antisocial behaviors, as well as poor school performance or problems in school (Cardona & Trujillo, 2022;Ortega et al, 2016).…”
mentioning
confidence: 92%
“…In addition, Borschmann et al, (2020) found that adolescents offenders in custody may face several significant health problems and a higher prevalence rate to conditions and risks such as mental disorders, substance use disorders, neurodevelopmental disabilities, infectious diseases, among others that in addition to impacting their physical and mental health directly impacts their education by placing them at a disadvantage with adolescents who do not have these conditions. In other studies, it has been found that this population has multiple risk factors that may be involved in the recidivism of crimes among those involved are the parents of adolescents by allowing or having a passive or permissive attitude regarding drug use, criminality in family members and antisocial behaviors, as well as poor school performance or problems in school (Cardona & Trujillo, 2022;Ortega et al, 2016).…”
mentioning
confidence: 92%